Knowledge retention of medical technology interns from semestral and trimestral school : a comparative study - Balbin, Aerielle Paula B.; Enriquez, Yhanzie D.; Ramos, Aloysius Dominic F.; Suarez, Elisha Joelle P.; Zuniga, Marjorie R. (Manila : National University, 2023)
This study aimed to determined the significant difference in academic performance between medical technology interns from trimestral schools and semestral school.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary of Findings, Conclusions and Recommendation -- References.
Includes bibliographical references.